Acute and sub-acute toxicity assessment of hibiscus rosa-sinensis L. methanol extract on skin cell - Abd Hamid, Muhammad Asyraf (2016)
Hibiscus rosa-sinensis L is known as hibiscus used as an herb in Ayurvedic or alternative medicine in India to treat variety of conditions. Many studies have been done in the past to study the pharmacological potential of such herbs. However, little investigation has been done in potential toxicities assessment of such products. There is now increase in evidence that many herbal medicines cause serious toxicity to their applicants. Two studies were conduct, acute and sub-acute toxicity studies. BJ fibroblast skin cells (CRL 2522) were plated into a 96 wells containing 2 control group and l treatment group. Aseptically, positive control were treated with 5% hydrogen peroxide, negative control was treated with the vehicle only. For acute toxicity, 5 wells were treated with 35, 39, 45, 50, 55 mg/ml extract. Plates were incubated (3 7°C 5% CO2) for 24 hours. For sub-acute toxicity, and 3 wells were treated with 20, 39, 78 mg/ml extract. Plate were incubated (37°C 5% CO2) for 4 hours before treatment were replaced with media for 1 hour and repeated 4 times within 24 hours. Morphological assessment was conducted using the light microscope. Viability of the cells were assessed by dilute with tetrazolium salt solution for 4 hours and spectrophotometrically measured. Treated cells with Hibiscus rosa-sinensis Linn extract show morphological changes and also reduces the skin cell viability as the concentration of the extract increases compared to the non-treated cells. In conclusion, the extract treatment shows signs of acute and sub acute toxicity on the BJ fibroblast skin cells at a very high concentration.